Sertifikasi Halal di Indonesia: Analisa Program Self-Declare dan Kesadaran Penggunaan Label Halal - Lailatul Fadilah; Slamet Slamet; Umi Julaihah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Indonesian government inaugurated the Badan Penyelenggara Jaminan Produk Halal (BPJPH) as an institution responsible for handling and issuing halal certificates based on the fatwa of the Majelis Ulama Indonesia (MUI). In line with this, the government issued the Indonesian halal label to replace the MUI halal label. There are pros and cons to the presence of the new halal label, such as the logo, which is considered Java-centric and less effective than the previous label and is perceived as inferior to halal labels from other countries. Additionally, a high level of error was found among halal-certified MSME actors in Losari Village, including those bearing the Indonesian halal label. The purpose of this study was to determine the reasons why many MSME actors, as participants in free halal certification (SEHATI), still include the Indonesian halal label. This study is a descriptive qualitative research study, with data collection conducted through interviews and observations. The results of the study indicate that the reasons why many MSME actors have not included halal labels according to standards are due to a lack of information and education from PPH facilitators, as well as the low skills of MSME actors in using technology.